Legislación y medicina en torno a los accidentes del trabajo en Chile 1900 – 1940 - Diego Ortúzar (Nuevo mundo - Mundos Nuevos, 2013)
The paper addresses the Chilean government’s principal measures regarding accidents in the workplace between 1900 and 1940. The period considers the progression from an absence of legal and sanitary safeguards of the working class in the early twentieth century, to the establishment of a legal regime, which administrated economical and medical assistance to the victims of workplace accidents. This route shows the emergence and transformations of said protection system and demonstrates that the emphasis of the government’s responses to workplace accidents was compensatory and restorative rather than preventive. This conclusion is suggested by the rise in numbers of accidents, the insufficient workplace safety measures and the significant investment in hospital infrastructure